2018
DOI: 10.18295/squmj.2017.17.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between Planned and Actual Operating Room Turnaround Times at a Large Rural Hospital in Germany

Abstract: abstract:Objectives: While several factors have been shown to influence operating room (OR) turnaround times, few comparisons of planned and actual OR turnaround times have been performed. This study aimed to compare planned and actual OR turnaround times at a large rural hospital in Northern Germany. Methods: This retrospective study examined the OR turnaround data of 875 elective surgery cases scheduled at the Marienhospital, Vechta, Germany, between July and October 2014. The frequency distributions of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The participants in the study declared that complex cases cannot have 30 min of turnaround time. These findings were in line with previously described findings of Morgenegg et al (2017) , which concluded that OR turnaround times were essentially influenced by the time of the surgical procedure, age of the patient, staffing changes, length of the surgery, and the utilization of equipment and materials requiring additional preparation time.…”
Section: Discussionsupporting
confidence: 91%
“…The participants in the study declared that complex cases cannot have 30 min of turnaround time. These findings were in line with previously described findings of Morgenegg et al (2017) , which concluded that OR turnaround times were essentially influenced by the time of the surgical procedure, age of the patient, staffing changes, length of the surgery, and the utilization of equipment and materials requiring additional preparation time.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, surgeries performed on patients between 20 and 29 years and above 50 years had either 40% or more underestimation, which correlates with the published findings stating that older patients did encounter prolonged surgeries. [38][39][40] A study revealed that surgeries performed on patients older than 65 years had 6 minutes increase in nonoperative time. 39 In addition to gender, age is essential in improving the accuracy of predicting surgery duration.…”
Section: Discussionmentioning
confidence: 99%